Safety and Efficacy of Continuous Infusion of a Combined Factor VIII – von Willebrand Factor (vWF) Concentrate (Haemate-P™) in Patients with von Willebrand Disease - Lubetsky, Aharon; Schulman, Sam; Varon, David; Martinowitz, Uri; Kenet, Gili; Gitel, Sanford; Inbal, Aida (Thrombosis and Haemostasis, 1999)
We studied the safety and efficacy of treatment with continuous infusion of a von Willebrand factor (vWF) concentrate Haemate-P in patients with von Willebrand disease (vWD). Three patients with mild and 5 patients with severe forms of vWD, were treated with continuous infusion of Haemate-P by minipump. The indications for treatment were: to prevent bleeding during 9 surgical procedures or 1 vaginal delivery in 6 patients and to treat 2 bleeding episodes in 2 patients. The patients were monitored daily for factor VIII (FVIII:C) and ristocetin cofactor (vWF:RCo) levels and the infusion rate was adjusted to maintain the desired therapeutic level of vWF:RCo. The treatment was effective in preventing surgical bleeding and controlling bleeding episodes. All factor VIII:C and most of the vWF:RCo levels measured during the study period were above the target therapeutic levels. A significant decrease in clearance of FVIII:C and vWF:RCo was observed over the treatment period. Haemate-P consumption averaged 24.3 ± 7.9 vWF:RCo U/kg/day which is approximately half the expected dose had intermittent bolus injections been used. We suggest that continuous Haemate-P infusion is superior to intermittent bolus injections for the treatment of vWD patients by virtue of its efficiency, simplicity and considerable savings.